2013
DOI: 10.1038/onc.2013.345
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-mediated transcriptional upregulation of TNFAIP2 by the Epstein–Barr virus oncoprotein, LMP1, promotes cell motility in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC), which is closely associated with Epstein-Barr virus (EBV), is a metastasis-prone epithelial cancer. We previously showed that tumor necrosis factor α-induced protein 2 (TNFAIP2) is highly expressed in NPC tumor tissues and is correlated with metastasis and poor survival in NPC patients. However, the underlying mechanism remains unclear. In this study, we demonstrate that the EBV oncoprotein, latent membrane protein 1 (LMP1), can transcriptionally induce TNFAIP2 expression via NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 53 publications
6
46
0
2
Order By: Relevance
“…LMP1 is capable of increasing cell motility and promoting metastasis (5,44). In agreement with these observations, LMP1 expression increased Rat1 cell migration by roughly 3-fold compared to pBabe vector control cells in a transwell assay (Fig.…”
Section: Lmp1 Expression Increases Igf1r Activationsupporting
confidence: 73%
“…LMP1 is capable of increasing cell motility and promoting metastasis (5,44). In agreement with these observations, LMP1 expression increased Rat1 cell migration by roughly 3-fold compared to pBabe vector control cells in a transwell assay (Fig.…”
Section: Lmp1 Expression Increases Igf1r Activationsupporting
confidence: 73%
“…The correlation between these pathways and multiple diseases including NPC has been proved by previous studies. Among which, apoptosis [33,34,35], p53 [36,37] and NF-κB [38,39] have been reported to be closely related to NPC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NF-κB-mediated transcriptional upregulation of TNFAIP2 by the Epstein-Barr virus oncoprotein, LMP1, promotes cell motility in NPC (20). However, few studies have shown that TNFAIP1 inhibits the transcriptional activities of NF-κB (25).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TNFAIP1 was found to be downregulated by miR-372/-373 and participates in cell apoptosis and proliferation via the NF-κB pathway (18,19). In addition, TNFAIP2 was found to promote tumor progression in nasopharyngeal carcinoma (NPC) (20), while knockdown of TNFAIP2 was found to markedly reduce the migration and invasion of NPC cells (15). The present study also showed that knockdown of TNFAIP1 repressed cell proliferation and invasion, and induced cell apoptosis in OS cells, which is supported by data that TNFAIP2 can mediate the inhibitory effects of retinoic acid on endometrial cancer cell growth, invasion and apoptosis escape (21), suggesting TNFAIP1/2 as a potential target for retinoic acid in acute promyelocytic leukemia (22).…”
Section: Discussionmentioning
confidence: 99%